Seasonal and annual variation in the abundance of Tiphia wasps (Hymenoptera: Tiphiidae) in Panama - Cambra, Roberto A.; Añino, Yostin J.; Windsor, Donald M.; Pickering, John; Romero, Emilio; Kimsey, Lynn S. (ENTOMOTROPICA, 2025)
We present the first records on seasonal and annual variation in the abundance of Tiphia wasps in the understory of a Neotropical Forest based on catches from 10 Malaise traps monitored weekly on Barro Colorado Island, Panama over three years (2003-2005). A total of 396 specimens of Tiphiidae were collected (351 males and 45 females), 201 individuals from year one, 65 from year two and 130 from the final year. Eight species were identified in the total catch, with the two most numerous species, Tiphia pacozo Allen, 1964 and T. panamaensis Allen, 1964 contributing with 311 and 35 specimens, respectively. Tiphia were most abundant in collections made during October and November 2003-2005, with an additional peak of abundance occurring in July 2005. We conclude that Tiphia display strong seasonal variations in abundance, with peaks occurring during the rainy season.